A numerical study on the angle of attack to the blade of a horizontal-axis offshore floating wind turbine under static and dynamic yawed conditions. (1st February 2019) - Wen, Binrong; Tian, Xinliang; Dong, Xingjian; Peng, Zhike; Zhang, Wenming; Wei, Kexiang
Abstract: The offshore floating wind turbines (OFWT) inevitably experience yawed flows, which result in fluctuations in the angle of attacks (AOAs) of the airfoils and therefore considerably impact the aerodynamics. In this paper, the AOA of the blade of a horizontal OFWT under static and dynamic yawed conditions are investigated using the Free Vortex Method (FVM). Results show that the AOA fluctuation under yawed conditions could be attributed to three effects: the blade advancing & retreating effect, the non-uniform induction effect and the upwind & downwind yawing effect. At a positive yaw angle, the blade advancing & retreating effect results in a maximum AOA at the azimuth of 0°. This effect is more dominant for the inboard airfoils than the outboard ones. The non-uniform induction effect results in a maximum AOA at 90° for inboard airfoils while at 270° for outboard ones. This effect is more evident for the outboard blade segments. When the OFWT experiences platform yawing motion or during the dynamic yawing process, the upwind & downwind yawing effect occurs. This effect increases the AOA when the blade is yawing upwind and vice versa. It is more dominant for outboard airfoils and it increases as the yawing rate augments. Highlights: The AOAs of an OFWT in static and dynamic yawed flows are studied with FVM. The unsteady effects causing AOA variation in yawed flows are revealed. The blade advancing & retreating effect is enhanced at inboard airfoils and lower TSRs. The non-uniform induction effect is stronger at outboard airfoils and higher TSRs. The upwind & downwind yawing effect increases with the yawing rate.